2017
DOI: 10.1002/aet2.10070
|View full text |Cite
|
Sign up to set email alerts
|

The View From the Top: Academic Emergency Department Chairs’ Perspectives on Education Scholarship

Abstract: Education scholarship continues to grow within emergency medicine (EM) and in academic medicine in general. Despite a growing interest, would-be education scholars often struggle to find adequate mentorship, research training, funding, and protected time to produce rigorous scholarship. The ways in which individual academic EM departments can support this mission remains an area in need of description.Objectives: We sought to describe academic EM department chairs' perceptions of education scholarship and faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…In the investigated context, teacher-centered and discipline-based approaches were dominant, so, there are no facilities, equipment and physical space needed to implement innovative approaches in teaching and assessment processes. In line with present results, time, educational infrastructure, and available resources were the perceived challenges by educators to implement educational scholarship in Clarke's study (22). Developing collaboration with coworkers, sharing skills and resources, creating peer and systemic support and developing motivational factors have been introduced as strategies for resolving the challenges of implementing scholarly project (13,21) that needs to be considered in the investigated context.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the investigated context, teacher-centered and discipline-based approaches were dominant, so, there are no facilities, equipment and physical space needed to implement innovative approaches in teaching and assessment processes. In line with present results, time, educational infrastructure, and available resources were the perceived challenges by educators to implement educational scholarship in Clarke's study (22). Developing collaboration with coworkers, sharing skills and resources, creating peer and systemic support and developing motivational factors have been introduced as strategies for resolving the challenges of implementing scholarly project (13,21) that needs to be considered in the investigated context.…”
Section: Discussionsupporting
confidence: 80%
“…The problems compelled some participants to change their subject of scholarly project. The mismatch between existing expectations and resources, as well as the misalliance between the ideal situation and what is applicable in the real environment exacerbates the scholarship challenges (21,22). In the investigated context, teacher-centered and discipline-based approaches were dominant, so, there are no facilities, equipment and physical space needed to implement innovative approaches in teaching and assessment processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized in programs aimed at maintaining and fostering academic careers at various universities. (23,24) This method also depends on how representative university staffs are. In this study, women reported a motivation to pursue a university career in Emergency Medicine that was as strong as men's.…”
Section: Discussionmentioning
confidence: 99%
“…As the academic job market in EM has become more competitive, fellowship training among applicants is increasingly becoming the norm . Within the sphere of medical education, chairs in EM have expressed a growing recognition of the importance of education research, as well as the need for well‐trained education researchers . However, while there are an increasing number of medical education fellowships, only a limited number are primarily focused on education scholarship.…”
Section: Advances In Medical Education Scholarshipmentioning
confidence: 99%